Business Model Exploration Using SWOT and Business Model Canvas at Djaya Store - Yoga Pamungkas, Maulana; Soepritjatno, Edy Djoko (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research purposes :This study aims to develop an effective business model at Djaya Grocery Store Design/Method/Approach :The method used in this study is a qualitative approach with data collection techniques through interviews, observations, and document analysis. In this study, the data source comes from the SWOT and BMC analysis process while the object of the study is Toko Djaya Research Findings:The research findings reveal that the development of a SWOT and BMC-based business model can be applied to the Djaya grocery store. Theoretical contribution/Originality: This study provides theoretical contributions by integrating SWOT analysis and Business Model Canvas in the context of developing business models for small businesses, especially grocery stores. Practitioner/Policy Implications:The practical implications of this study are to provide recommendations for the owner of Sembako Djaya Store to optimize stock management, improve marketing through digital platforms, and build better relationships with customers. Research limitations: The limitations of this study include the limited focus on one grocery store, so the results may not be generalizable to all similar businesses.